2009
DOI: 10.1111/j.1365-2222.2008.03184.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of adverse reactions to food in German adults

Abstract: From a general population survey conducted in Germany, we determined that women are at greater risk of having symptoms of food allergy and also at greater risk of having DBPCFC-confirmed symptomatic food allergy. However, among individuals with symptoms of food allergy, men have a higher prevalence of food-specific IgE-sensitization and of raised total IgE than women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
4
25
1
2
Order By: Relevance
“…Studies addressing the characteristics of persons with SFH indicate a female predominance [16, 17]. They further suggest that young women with higher education more often report adverse reactions to food than older women with lower education [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies addressing the characteristics of persons with SFH indicate a female predominance [16, 17]. They further suggest that young women with higher education more often report adverse reactions to food than older women with lower education [17].…”
Section: Introductionmentioning
confidence: 99%
“…They further suggest that young women with higher education more often report adverse reactions to food than older women with lower education [17]. Another study indicated that individuals with SFH are more often absent from work, but that only 2% of that study sample felt that their income had been affected due to food-attributed symptoms [18].…”
Section: Introductionmentioning
confidence: 99%
“…The actual prevalence seems to be lower: approximately 5-8% of children and 2-3% of adults suffer from objective food hypersensitivity [19] .…”
mentioning
confidence: 99%
“…Some studies suggest that females might suffer from adverse reactions to food more often than males [19,20] .…”
mentioning
confidence: 99%
“…Weiterführende allergologische Untersuchungen bei 27 Patienten mit Durchfüh-rung einer Nahrungsmittelprovokation bei 9/27 Patienten führten am Ende in lediglich 4 Fällen zur Diagnose einer Nahrungsmittelallergie. In einer weiteren ähn-lich konzipierten Studie konnte allgemein ein höheres Risiko für eine Nahrungsmittelallergie für Frauen (Punktprävalenz 3,3%) im Vergleich zu Männern (Punktprävalenz 1,8%) ermittelt werden [54].…”
Section: Prävalenz Und Krankheitsverlaufunclassified